EFEKTIVITAS MEDIA AUDIOVISUAL PADA PEMBELAJARAN MENGIDENTIFIKASI STRUKTUR DAN UNSUR-UNSUR DRAMA SISWA KELAS XI MAN 1 SLEMAN T.A 2017/2018 - Hapsari Retno Kinasih; Siti Rochmiyati (CARAKA, 2018)
The purpose of this descriptive study is twofold, namely, to describe the extent to which the tendency to identify the structure and elements of drama on the student of Class XI MAN 1 Sleman which analytical study using audiovisual media and media print. Comparatively to find out significant differences between the use of audiovisual media and print media towards the ability to identify the structure and elements of drama. This research population totaled 196 students. Sample research with simple random sampling technique. Research results improve student descriptive distribution on identifying the structure and elements of drama with audiovisual media average 29,74 category is very high and the average print media with 27,12 category is also very high. Comparatively =4,253 Â 1,672 so, Ha is accepted and Ho is rejected.